An Analysis of major Business in Today's High school Sports - Ayesha Firdos; Muhammad TALAL Ahmad, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
This research study measures the analysis related to significant business in today's high school sports. This research was conducted in China and describes the major business in today's high school. The research study based on primary data analysis for gathering the data used specific questions related to the variables included major business, high school sports activities included a commitment of sports activities, the time spent on Sport, etc. These are all considered variables for gathering the data used 100 plus respondent participants related to the high school sports and businessman of sports industries. Measuring the data used different techniques and run informative results; for this purpose, smart PLS software was used to run informative results. Descriptive statistical analysis, the correlation coefficient, regression, and model fitness analysis also describe that reliability, validity, and graphical analysis related to the major business in today's and sports activities of high school performance. The overall result shows a significant relationship between the significant business and high school sports related to the commitment of sports activities.